Integration of Dapodik Data, EMIS Data, and Dukcapil Data in Supporting Synchronization of School Participation Figures (APS) Muaro Jambi Regency Government - Yanto; Hamdi, Muhamad (Jurnal Prajaiswara, 2024)
Abstract— Introduction/Main Objectives: This research examines the synchronization of School Enrollment Rate (APS) data in Muaro Jambi Regency, addressing inconsistencies between Dapodik, EMIS, and population data.. Novelty: The study offers a novel approach by integrating these data sources to enhance synchronization. Research Methods: Using a descriptive qualitative approach, the research identifies obstacles and proposes solutions for improving regional education information systems. Finding/Results: Findings reveal integration efforts through direct data management collaboration, periodic verification, and categorization of verification types. However, challenges such as inadequate internet infrastructure, computer performance issues, incomplete data attributes, and inefficient updating processes persist. Proposed solutions include an integrated data collection system for student transfers and standardized SOPs for data collection. Despite these efforts, APS data synchronization remains suboptimal, requiring further improvements to enhance accuracy and integration effectiveness. Enhanced data quality is crucial for developing and implementing targeted education policies in Muaro Jambi Regency. Conclusion: This study underscores the importance of overcoming technological and procedural barriers to achieve a more reliable and efficient APS data system, supporting better policy planning and execution in the region.